NiTi shape memory alloy thin film based microgripper - Tan, Jun Ping. (2008)
The objectives of this project are to produce NiTi thin film that exhibits Shape Memory Effect (SME) onto a cantilever beam and to produce a microgripper of size about 750x350x350 micrometer using the cantilever structure.